IMF Survey : Volume 29, Issue 20. (IMF Survey; IMF Survey ;, 2000)
In conjunction with its annual Article IV consultation with Japan, IMF staff prepared a background paper (Japan-Selected Issues) on a number of key topics. Two chapters of that paper dealt with the macroeconomic and fiscal implications of Japan's aging population. The authors-Hamid Faruqee, an Economist in the Research Department, and Martin Muhleisen, an Economist in the Asia and Pacific Department-speak with the IMF Survey about their findings.